An extended assessment of fluid flow models for the prediction of two-dimensional steady-state airfoil aerodynamics - Herbert Acero, José F.; Probst, Oliver; Rivera Solorio, Carlos I.; Castillo Villar, Krystel K.; Méndez Díaz, Santos (2015)
This work presents the analysis, application, and comparison of thirteen fluid flow models in the prediction of two-dimensional airfoil aerodynamics, considering laminar and turbulent subsonic inflow conditions. Diverse sensitivity analyses of different free parameters (e.g., the domain topology and its discretization, the flow model, and the solution method together with its convergence mechanisms) revealed important effects on the simulations’ outcomes. The NACA 4412 airfoil was considered throughout the work and the computational predictions were compared with experiments conducted under a wide range of Reynolds numbers (7